Pacific dominance to global air-sea CO2 flux variability: A novel atmospheric inversion agrees with ocean models - McKinley, GA; Rodenbeck, C; Gloor, M; Houweling, S; Heimann, M (Geophysical Research Letters, 2004)
We address an ongoing debate regarding the geographic distribution of interannual variability in ocean-atmosphere carbon exchange. We find that, for 1983-1998, both novel high-resolution atmospheric inversion calculations and global ocean biogeochemical models place the primary source of global CO2 air-sea flux variability in the Pacific Ocean. In the model considered here, this variability is clearly associated with the El Nino/Southern Oscillation cycle. Both methods also indicate that the Southern Ocean is the second-largest source of air-sea CO2 flux variability, and that variability is small throughout the Atlantic, including the North Atlantic, in contrast to previous studies.